Interferon Regulatory Factor 5 in the Pathogenesis of Systemic Lupus Erythematosus - Candace M. Cham; Kichul Ko; Timothy B. Niewold (Clinical and Developmental Immunology)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by multiple genetic risk factors, high levels of interferon alpha (IFN-α), and the production of autoantibodies against components of the cell nucleus. Interferon regulatory factor 5 (IRF5) is a transcription factor which induces the transcription of IFN-α and other cytokines, and genetic variants of IRF5 have been strongly linked to SLE pathogenesis. IRF5 functions downstream of Toll-like receptors and other microbial pattern-recognition receptors, and immune complexes made up of SLE-associated autoantibodies seem to function as a chronic endogenous stimulus to this pathway. In this paper, we discuss the physiologic role of IRF5 in immune defense and the ways in which IRF5 variants may contribute to the pathogenesis of human SLE. Recent data regarding the role of IRF5 in both serologic autoimmunity and the overproduction of IFN-α in human SLE are summarized. These data support a model in which SLE-risk variants of IRF5 participate in a “feed-forward” mechanism, predisposing to SLE-associated autoantibody formation, and subsequently facilitating IFN-α production downstream of Toll-like receptors stimulated by immune complexes composed of these autoantibodies.